Glioma neuron symbiosis: a hypothesis - Schurr, Avital (Frontiers in Neuroscience, 2025)
Glioma cells, just like all cancerous cells, consume substantial amounts of glucose for their energy needs, using glycolysis, an inefficient metabolic pathway (Warburg effect) to produce only two moles of adenosine triphosphate and two moles of lactate for each mole of glucose consumed. By contrast, neurons consume glucose via glycolysis and utilize its end-product lactate as the substrate of the mitochondrial tricarboxylic acid cycle and its coupled oxidative phosphorylation, a process eighteen times more efficient at adenosine triphosphate than glycolysis alone. It hypothesizes here that glioma-produced lactate is the preferred oxidative energy substrate of their surrounding neurons. Consequently, by using lactate, neurons bypass glycolysis, sparing their glucose and making it readily available for the glucose-craving cancer cells. Moreover, glioma cells’ ability to secrete glutamate, which excites glutamatergic neurons, could drive the latter to consume even more lactate, sparing more glucose. Such symbiotic exchange, especially at the initial stages of malignancy, assures the budding cancer cells an ample glucose supply ahead of the development of additional vasculature. While this hypothesis focuses on gliomas, it may also apply to other cancer types.